2006
DOI: 10.1216/rmjm/1181069462
|View full text |Cite
|
Sign up to set email alerts
|

Integrability of Planar Polynomial Differential Systems through Linear Differential Equations

Abstract: In this work, we consider rational ordinary differential equations dy/dx = Q(x, y)/P (x, y), with Q(x, y) and P (x, y) coprime polynomials with real coefficients. We give a method to construct equations of this type for which a first integral can be expressed from two independent solutions of a second-order homogeneous linear differential equation. This first integral is, in general, given by a non Liouvillian function.We show that all the known families of quadratic systems with an irreducible invariant algeb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 24 publications
1
53
0
Order By: Relevance
“…The transformation method we shall apply is derived in [6]. For the sake of completeness, we summarize it here and give some remarks.…”
Section: Statement Of the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transformation method we shall apply is derived in [6]. For the sake of completeness, we summarize it here and give some remarks.…”
Section: Statement Of the Methodsmentioning
confidence: 99%
“…Comparing with (6) we see that the coefficient of y 4 must be b k4 x k , which determines c as follows:…”
Section: Application To Kukles Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation permits the generalization of the DarbouxÕs integrability theory given in [59,60] where a new kind of first integrals, not only the Liouvillian ones, is described. In [63] it is showed that a transformation method relating planar differential systems to second order linear equations is an effective tool for finding non-Liouvillian first integrals. The problem of finding a first integral for system (1) and the functional class that it belongs to is what we call the integrability problem.…”
Section: Invariant Algebraic Curvesmentioning
confidence: 99%
“…Many examples of invariants with a quasipolynomial cofactor are given in [9] as well as a method to find first integrals, which are non-Liouvillian in general, for certain families of systems.…”
Section: ·1 Particular Algebraic Solutionsmentioning
confidence: 99%